Histological Appearance of Placental Solomonization in the Treatment of Twin–Twin Transfusion Syndrome - Emery, Stephen P.; Nguyen, Lananh; Parks, W. Tony (American Journal of Perinatology Reports, 2016)
Background Placental laser equatorialization or “solomonization” during treatment for twin–twin transfusion syndrome (TTTS) is associated with improved pregnancy outcomes. Concern exists, however, about the extent of placental injury caused by the technique, and of its ability to create “dichorionization,” or complete separation of the fetal vascular circuits.Case Study A “solomonized” placenta was histologically examined for depth of cell damage. Solomonization produces complete devascularization of the chorionic plate, but has minimal effect on the underlying villi. The median depth of the effect was 2,823 µm, or < 3 mm.Conclusion Solomonization produces complete devascularization of the chorionic plate, but has little effect on the underlying villi. “Dichorionization” is therefore not achieved. Ongoing surveillance of treated pregnancies is warranted.
Keywords: laser photocoagulation; placental equatorialization; Solomon technique; twin–twin transfusion syndrome